Raising environmental awareness through community-based efforts to clean and preserve the Karang Mumus river, Samarinda City - Intan Kinanthi Damarin Tyas; Devy Indah Paramitha; Jeane Betty Kurnia Jusuf (Community Empowerment, 2024)
River pollution, particularly from littering, has long plagued Samarinda City. The Karang Mumus River exemplifies this challenge, with heavy downstream debris and a lack of upstream catchment areas leading to seasonal flooding. This pollution significantly reduces the community's quality of life and hinders sustainable development efforts. To address this, a community service program was initiated to raise environmental awareness through cleaning and maintaining the Karang Mumus River. The program utilized outreach methods to educate the "Save Karang Mumus" (SKM) community about the river's functions and proper environmental practices in the surrounding area. The activity culminated in a river cleaning initiative. Notably, post-program participants expressed a willingness to actively participate in future river cleaning efforts organized by GMSS-SKM. This positive outcome demonstrates the program's success in raising awareness about the importance of protecting the Karang Mumus River environment.